Autistic and Psychopathic Traits among a Community-based Sample of Adults. Issue 8 (3rd August 2021) - Barnard-Brak, Lucy; Richman, David M.
ABSTRACT: Little is known about the shared and separate traits for adults diagnosed with some form of psychopathy and autism. The primary distinction between a person with autism versus psychopathy is that a person with autistic traits is often unaware that their behavior is aversive to other people while a person with psychopathic traits is typically can articulate that their behaviors inflict pain or discomfort on other people they but still exhibit the offensive behavior. The primary purpose this was to examine the relation between psychopathic and autistic traits among a general population sample of adults. Next, we examined for overlap (or shared variance) and differences in psychopathy scores among individuals who met the ASD screening score cutoff, high levels of psychopathy traits, or both high levels of ASD and psychopathy traits. Results suggested that individuals of with high levels of ASD traits had the most severely impaired social interaction skills, while people with high levels of psychopathy traits had the highest levels of restricted and repetitive behavior. These preliminary results are discussed in terms of implications for future research on the possible comorbidity of autism and psychopathy traits, and how these two historically separate research literatures may benefit from collaboration across investigators in these two fields of mental disorders.